Upaya Meningkatkan Kemandirian Belajar Matematika sebagai Pilar Pendidikan Karakter di Tingkat SMP: Tinjauan Literatur - Roy, La; Peni, Nur Robiah Nofikusumawati (Prodi Pendidikan Matematika FKIP Universitas HKBP Nommensen, 2024)
This article highlights the urgency of enhancing mathematics learning independence as a pillar of character education at the junior high school level. Focusing on students' lack of learning independence, the article explains the relevance of a positive attitude towards independent learning in the context of mathematical literacy. The article provides study findings that address influences on children's learning independence and achievement, including peer environment, learning motivation, family social interaction and school tactics, through a literature review. The findings demonstrate the important impact of learning independence in improving academic achievement. Improving learning independence can be done through the application of contextual learning models, social environment and parental support. This study offers several solutions, including the creation of creative learning models, evaluation of curriculum implementation that emphasizes learning independence, and interventions that focus on the causes of low independence. Future research is expected to make a real contribution in advancing mathematics learning independence at the junior high school level.